The Development of English Policy in Pakistan (Journal of Interdisciplinary Insights, 2024)
The origins of Pakistan's English policy are rooted in the period of British colonial rule, during which English was established as a symbol of authority. Upon gaining independence, Pakistan adopted Urdu as the national language to forge a cohesive national identity. However, the designation of Urdu sparked linguistic tensions among various ethnic groups within the country. In response, English was designated as an official language, serving as a neutral medium amidst these disputes. As economic globalization progressed, the Pakistani government prioritized English education to bridge social class disparities through its democratization. In September 2015, the Supreme Court of Pakistan declared that the official language would revert to Urdu, in compliance with the 1973 Constitution. The current English policy in Pakistan is characterized by pragmatism, evident in the de-emphasis of English in governmental affairs and the promotion of its accessibility in educational settings. Despite these intentions, the implementation of this pragmatic approach has been inconsistent, potentially leading to unexpected consequences. The effectiveness of this policy in achieving its goals of social equity and linguistic harmony remains a subject of ongoing evaluation and debate.